A 2.45 GHz Harmonic Suppression Rectangular Patch Antenna With Circular Polarization For Wireless Power Transfer Application - Zainol, Nurzaimah; Zakaria, Zahriladha; Abu, Maisarah; Mohamed Yunus, Mawarni (Taylor & Francis Group., 2017)
This paper presents a 2.45 GHz harmonic suppression rectangular patch antenna with circularly polarized for wireless power transfer applications. The miniaturized proximity-coupled antenna has the advantage of excellent higher harmonic suppression of up to −3 dB at harmonic frequency. This characteristic is achieved by introducing a U-slot and the symmetrical arm of inverted U-stub embedded on the transmission feed line. The overall size of the proposed antenna gives 36% reduction of substrate area as compared to conventional designs. The antenna is designed, optimized, and simulated on FR-4 substrate of dielectric constant 4.3, loss tangent 0.019, and height 1.6 mm offering moderate gain and good axial ratio of 1.48 dB. Details of the simulated and experimental characteristics of the antenna are presented and discussed.